Eco-Healing Tourism dan Kontribusinya Terhadap Keberlanjutan Destinasi Wellness di Tabanan, Bali - Putu Eka Wirawan; Komang Trigita Juliastari (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2026)
The development of global tourism has shifted toward experience-based, health-oriented, and sustainable tourism, leading to the emergence of eco-healing tourism as an integration of wellness activities and interaction with natural environments. Tabanan Regency, Bali, possesses significant natural landscape potential to support this type of tourism; however, its utilization remains fragmented and not yet integrated into a sustainable destination framework. This study aims to analyze the contribution of eco-healing tourism to the sustainability of wellness destinations in Tabanan, Bali. The research employs an interpretive qualitative approach using field observations, in-depth interviews, and documentation, with thematic analysis applied to the data. The findings reveal that eco-healing experiences are constructed through sensory, emotional, and reflective dimensions that provide restorative benefits to tourists while implicitly encouraging digital detox practices. From a sustainability perspective, eco-healing tourism has the potential to support environmental conservation, enhance tourist awareness, and create economic opportunities for local communities. However, these contributions remain suboptimal due to the lack of integrated destination management. This study highlights the strategic role of eco-healing tourism in developing sustainable wellness destinations and offers practical implications for stakeholders in designing adaptive, inclusive, and sustainable tourism models. Keywords: eco-healing tourism, wellness destination, sustainability, tourist experience